Aktivitas Antibakteri Ekstrak Daun Benalu Jambu Air (Dendropthoe pentandra (L.) Miq) Terhadap Pertumbuhan Salmonella typhi - Ari Hepi Yanti, Arbet Anita, Siti Khotimah, (Universitas Tanjungpura, 2014)
Dendropthoe pentandra (L.) Miq constitutes one type of parasite plant, which is efficacious as an antibacterial and able to inhibit the growth of microorganisms. Salmonella typhi is the bacteria that attacks the gastrointestinal tract, so that it is necessary to look for antibacterial alternative medicine from natural materials. The aim of this study is to determine the antibacterial activity of methanol extract from D. pentandra leaves toward the growth of S. typhi bacteria. The research conducted from August to September 2013. The extract of D. pentandra leaves obtained by employing maceration method. The test of antibacterial activity carried out by using paper disc diffusion method at the level 25%, 50%, 75% and 100% (g/mL) of extract concentration, and also positive control by using 2.5% of chloramphenicol. Phytochemical analysis indicates that the extract of D. pentandra leaves contain flavonoids, alkaloids, polyphenols, steroids and quinones. The analysis indicates that the concentration of D. pentandra extract leaves has significant effect toward the diameter of the inhibition zone formed. Concentration of 75% is the lowest concentration that can inhibit the growth of S. typhi to grow larger. The results indicate that the methanol extract of D. pentandra leaves has antibacterial activity toward S. typhi.